Influence of dietary canola oil and palm oil blend and refrigerated storage on fatty acids, myofibrillar proteins, chemical composition, antioxidant profile and quality attributes of semimembranosus muscle in goats - Adeyemi, Kazeem Dauda; Sabow, Azad Behnan; Shittu, Rafiat Morolayo; Karim, Roselina; Sazili, Awis Qurni (BioMed Central, 2015)
Background: Improving the unsaturated fatty acid content of ruminant meat is essential due to the generally saturated nature of fatty acids in ruminant meat and the negative effects this can have on human health. Nonetheless, enhancing the unsaturated fatty acid content of ruminant meat can have adverse effects on the shelf life and quality attributes of the meat. This study assessed the effects of dietary 80 % canola oil and 20 % palm oil blend (CPOB) on fatty acid composition, antioxidants, oxidative spoilage, cholesterol and physicochemical properties of semimembranosus (SM) muscle from goats. Twenty four Boer bucks were randomly assigned to diets containing on dry matter basis 0, 4 and 8 % CPOB, fed for 100 d and slaughtered. The carcasses were subjected to a 7 d postmortem refrigerated storage. All analyses were conducted on the SM muscle. Results: Diet had no effect (P > 0.05) on the concentration of free thiol and carbonyl and the band intensity of myosin heavy chain, actin and troponin T. The muscle glycogen, pH, water holding capacity, tenderness, glutathione peroxidase (GPX) activity, total carotenoid, δ-tocopherol, cholesterol and proximate composition did not differ (P > 0.05) between diets. The SM muscle from goats fed 4 and 8 % CPOB had lower (P < 0.05) concentration of C14:0 and C16:0 and higher (P < 0.05) concentration of C18:1 trans-11, C18:1ω-9, C18:3ω-3, C20:5ω-3 and C22:5ω-3 than the SM muscle from the control goats. Dietary CPOB increased (P < 0.05) the concentration of α and γ tocopherol and meat redness (a*) on d 1 and 4 postmortem. Regardless of diet, antioxidant vitamins, and shear force decreased (P < 0.05) while drip loss, lipid and protein oxidation increased (P < 0.05) as postmortem storage progressed. Conclusion: Results evince that dietary CPOB can be used as a management tool to enhance the beneficial fatty acids and antioxidant contents of chevon without deleterious effects on its physicochemical properties and shelf life.